Territorial Delimitation Between Siberian Territory and Ural Region in 1923—1926 - K. B. Korzhenevsky (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
Based on a wide range of attracted archival materials, the problems of establishing the border line between the Siberian Territory and the Ural Region in the mid-1920s are examined in the article. The main controversial issues, which consisted in the discussion about the belonging of a part of the Tobolsk North and the Ishim District, which were part of the beginning of zoning in the Ural region are revealed. Attention is paid to the history of the emergence of border disputes that appeared as a result of the attribution of a number of West Siberian territories from the jurisdiction of Sibrevkom to the Urals in the early 1920s. A detailed description of the process of determining the western border of the Siberian Territory is given by the leadership of the Sibrevkom, as well as by the higher authorities of the RSFSR in close cooperation with the Ural and Siberian authorities. Various arguments of the Siberians, the Urals and the central authorities, used in the process of delimiting and resolving disputes between Siberia and the Urals, which make it possible to more objectively determine the legality of the established demarcation line are presented. It is concluded that the territorial claims of the Siberian leadership to the Ural authorities were justified and relied on the undefined status of the disputed sections of the border, which arose as a result of the temporary abandonment of the territory of the former Tyumen province by the central government as part of the Ural region formed in November 1923.